1999
DOI: 10.1590/s0066-782x1999000100002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic coronary artery disease

Abstract: State of the ArtCoronary insufficiency (CI) is the state in which an imbalance occurs between the supply and demand of oxygen, which prevents adequate maintenance of the metabolic needs of the myocardium, resulting in ischemia of several degrees of intensity.CI has numerous causes among which are cardiac valvular diseases (aortic stenosis), hypertrophic cardiomyopathy, microvasculature diseases (diabetes mellitus, syndrome X), anomalous origin of coronary arteries, and coronary fistulas. However, the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
3
Order By: Relevance
“…Previous studies have shown that visceral fat accumulation is associated with increased risk of CV risk [37]. In addition, with an increase in TNF- α , a reduction in lipoprotein lipase activity in adipose tissue is observed [39]. There is also evidence that TNF- α has a local effect, regulating adipocyte size in the face of increasing energy consumption [40, 41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that visceral fat accumulation is associated with increased risk of CV risk [37]. In addition, with an increase in TNF- α , a reduction in lipoprotein lipase activity in adipose tissue is observed [39]. There is also evidence that TNF- α has a local effect, regulating adipocyte size in the face of increasing energy consumption [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, such as TNF- α and IL-6, are primarily involved in the early stages of the inflammatory response culminating in atherosclerosis [39, 42]. Increased TNF- α levels in the endothelium promote initial atheroma plaque [39, 42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prazosina, um bloqueador seletivo de alfa-adrenorreceptores, também tem se mostrado eficaz em alguns pacientes, sendo considerada uma droga de segunda linha no tratamento da angina de Prinzmetal. 16 Um possível fator que contribui para o espasmo coronário é a deficiência de magnésio, pois este tem um efeito bloqueador nos canais de cálcio e pode prevenir a contração do músculo liso vascular. Daí a infusão de magnésio ser proposta para reduzir os ataques de espasmos nesses pacientes.…”
unclassified
“…Daí a infusão de magnésio ser proposta para reduzir os ataques de espasmos nesses pacientes. 16 Existe uma associação do uso do ácido acetilsalicílico com vasoespasmo coronariano, fato especialmente importante em pacientes que realizaram ICP prévia. A admi nistração de altas doses de aspirina (>325mg por dia) é conhecida por bloquear a produção de prostaciclina, que é um potente vasodilatador endógeno e, por tal motivo, pode agravar o vasoespasmo da artéria coronária, 17 porém mesmo a administração de baixas doses de aspirina é conhecida por bloquear o tromboxano A2, que também está implicado no espasmo da artéria coronária.…”
unclassified